The Ethics of AI in Education: An Empirical Study on Students’ and Teachers’ Attitudes toward Responsible AI Use - Nofirman, Nofirman; Vann, Rithy; Sefrizal, Levy; Dara, Ravi (Al-Hijr: Journal of Adulearn World, 2025)
The rapid integration of artificial intelligence (AI) into educational settings has outpaced the development of clear ethical guidelines, creating significant challenges related to academic integrity, data privacy, and algorithmic bias. Understanding stakeholder attitudes is crucial for developing effective policies for responsible AI use. This study aimed to empirically investigate and compare the attitudes of high school students and teachers regarding the ethical challenges and responsible use of AI in education. A mixed-methods approach was employed, using a quantitative survey administered to 250 students and 50 teachers to gauge attitudes toward AI ethics. This was supplemented by qualitative data from semi-structured focus groups to explore the reasoning behind these attitudes. The findings revealed a significant divergence in attitudes, with teachers expressing greater concern for academic integrity and data privacy, while students were more focused on AI as a tool for efficiency. Both groups, however, demonstrated a shared desire for clear, explicit ethical guidelines. A notable gap exists between student and teacher perspectives on AI ethics in education. To foster a culture of responsible AI use, educational institutions must implement comprehensive training and develop clear policies that address the distinct concerns of both stakeholder groups.